Language Learning Across the Life Course: A Qualitative Study of Digital Practices, Educational Transitions, and Intergenerational Experiences - Hamza‎ Andaloussi; Asubiojo Raphael Ojo (Digital Learning, Social Science, and Life-course Studies, 2025)
Digital technologies have transformed language learning by extending opportunities beyond formal education and promoting lifelong engagement. Despite growing research, studies often focus on specific contexts and short-term outcomes, offering limited insights into the longitudinal development of language learning across life stages. This study addresses this gap by using a qualitative life-history approach, informed by life-course theory, to explore how individuals experience and sustain digital language learning. Data were collected through semi-structured interviews with participants from various age groups and analyzed with narrative thematic analysis. The results show that digital language learning is a dynamic process, starting with early socialization in family and school, intensifying during key transitions, and continuing into adulthood through self-directed digital engagement. Intergenerational relationships and unequal access to digital resources influence learners’ opportunities, motivations, and orientations. These findings suggest that digital technologies not only enhance access and flexibility but also allow learners to adapt their language learning amid life disruptions. By integrating life-course and intergenerational perspectives, this study expands research that typically views learning as context-dependent. It offers implications for educational policies and digital learning frameworks, highlighting the need to recognize language learning as a lifelong process and address digital and intergenerational inequalities for inclusive, sustainable language learning.